Digging through the roots of addiction: Understanding the causes that underlie the insidious problem of substance use disorders (SUDs). - Evans, Christopher J. (Neurosci Biobehav Rev, 2019)
This issue features a selection of articles that explore mechanisms of processes that contribute to behaviors that are associated with addiction. We have identified selected articles which focus on the mechanisms underlying maladaptive consumption and affective dysregulation. In addition to the articles within this issue, we highlight the necessity of inclusive study design and acknowledgement of individual drug vulnerabilities.